2018
DOI: 10.1002/jper.18-0394
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis as another comorbidity associated with psoriasis: A case‐control study

Abstract: Background The association between periodontitis and immuno‐mediated inflammatory diseases has been widely studied and recognized each more over the past few years. The aim of this study was to evaluate the potential association between psoriasis and periodontitis, as well as the influence of risk variables in this association. Methods This case‐control study included 756 individuals, 397 with psoriasis, and 359 controls. A full‐mouth periodontal examination was performed, recording therefore plaque index, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(68 citation statements)
references
References 47 publications
(141 reference statements)
8
60
0
Order By: Relevance
“…Next, 215 records that were irrelevant to our topic were excluded after the titles and abstracts were screened, leaving 23 articles for a further full text review. Finally, 8 studies fulfilled the eligibility criteria and were included in this meta-analysis (20, 2228). The flow chart of the study selection process is displayed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Next, 215 records that were irrelevant to our topic were excluded after the titles and abstracts were screened, leaving 23 articles for a further full text review. Finally, 8 studies fulfilled the eligibility criteria and were included in this meta-analysis (20, 2228). The flow chart of the study selection process is displayed in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Many retrospective and case-control studies have reported an association between psoriatic diseases, mainly psoriasis vulgaris and psoriatic arthritis, and periodontal disease [95,96,97]. A large 5-year follow-up cohort study indicated that in psoriasis patients (psoriasis subtypes not specified), chronic periodontitis showed an incidence rate of 1.88 per 1000 patient-years compared to 1.22 in the control group [98].…”
Section: Th17/il-17 In Immunoprotection and Immunopathologymentioning
confidence: 99%
“…Periodontitis is an infectious inflammatory condition that causes destruction of dental supporting structures (Kinane & Bartold, ). Considering its complex pathogenesis, the susceptibility to periodontitis is related to disorders of the polymicrobial synergism that results in dysbiosis (Mendes, Cota, Costa, Oliveira, & Costa, ; Shaikh, Patil, Pangam, & Rathod, ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering its complex pathogenesis, the susceptibility to periodontitis is related to disorders of the polymicrobial synergism that results in dysbiosis (Mendes, Cota, Costa, Oliveira, & Costa, 2019;Shaikh, Patil, Pangam, & Rathod, 2018).…”
Section: Introductionmentioning
confidence: 99%